Inhibition of Acute Graft-versus-Host Disease with Retention of Graft-versus-Tumor Effects by Dimethyl Fumarate - Han, Jingjing; Ma, Shoubao; Gong, Huanle; Liu, Shuangzhu; Lei, Lei; Hu, Bo; Xu, Yang; Liu, Haiyan; Wu, Depei (Frontiers in Immunology, 2017)
Acute Graft-versus-host disease (aGVHD) remains a clinical challenge and a major source of morbidity and mortality following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Dimethyl fumarate (DMF), an activator of Nrf2, has been shown to have anti-inflammatory and immunomodulatory properties without significant immunosuppression. We therefore hypothesized that DMF could be potentially harnessed for the treatment of aGVHD with retention of GVT effect. In this study, we showed that DMF significantly inhibited alloreactive T cell responses in vitro in mixed lymphocyte reaction assay. Administration of DMF significantly alleviated the severity, histological damage, and the overall mortality of aGVHD in an MHC-mismatched aGVHD model. DMF administration reduced the activation and effector function of donor T cells in vitro and in vivo. In addition, DMF treatment upregulated antioxidant enzymes HO-1 and GST-α1 expressions. Furthermore, DMF treatment markedly increased the frequencies of Treg cells. Depletion of CD25+ cells in DMF recipients aggravated aGVHD mortality compared with IgG control recipients. DMF could promote Treg cell differentiation in a dose dependent manner by upregulating TGF-β expression in vitro. Most importantly, DMF administration preserved graft-versus-leukemia effect after BMT. In conclusion, our findings demonstrated DMF as a promising agent for the prevention of aGVHD after allo-HSCT.